Pakistan's political parties : surviving between dictatorship and democracy - Mufti, Mariam; Shafqat, Sahar; Siddiqui, Niloufer (Georgetown University Press, 2020)
"Pakistan's Political Parties provides a comprehensive overview of the country's major party politics and updates our understanding of Pakistan's evolving political system. The Pakistan general elections of 2018 marked the second successful transfer of power from one elected civilian government to another. This was only the second time in the country's history that a civilian government had completed its full five-year term in office. The contributors analyze the role of the military, bureaucracy, and judiciary in politics, but the major contribution of the volume is to refresh our understanding of how Pakistan's political parties are functioning and surviving in the country's improving though fragile democracy. Pakistan's parties are myriad and each represents a distinct interest from left, right, and/or populist to religion, region, ethnicity, reform, or some combination thereof. Studying their internal workings, motivations, mechanisms for influencing both state and society, and capacity to make policy provides an excellent opportunity to shed light on exactly how Pakistan's developing democracy functions. This book is one of a kind and will be the go-to reference for anyone interested in learning about politics in Pakistan"--